Conselho Tutelar Digital - Maia, Leonardo Figueiredo (2023)
The dissertation highlighted the relevance of ICTs in child protective councils, especially considering the underutilization of these tools in places like Marabá, Pará. The central focus was the proposition and development of an app to acquaint citizens with the child protective council of their city, introducing the councilors and providing a channel for reporting violations of child and adolescent rights. The methodology used involved the use of Flutter and Firebase technologies, ensuring the app's availability on different platforms and guaranteeing the security of data on Google's cloud. To deepen the understanding of the councilors' needs, interviews were conducted, which grounded and enriched the project's development. Despite facing challenges, such as financial constraints and local administrative decisions, the app stands out for being open source, available for implementation by any interested child protective council. The work was modified and adapted for the development of a simple app, with minimal investment in infrastructure. This initiative aims to improve the communication and work of the councils, establishing a direct and efficient link between the population and these bodies, thus ensuring greater protection of child and adolescent rights.